(untitled) - Hill, Charles W. (Boston, 2005)
Market-defining since it was first introduced, International Business 5e by Charles W. L. Hill, continues to set the standard for international business textbooks. In writing the book, Charles Hill draws on his expertise in teaching, writing, and consulting to create the most thorough, up-to-date, and thought-provoking text on the market. Because many issues in international business are complex, the text explores the pros and cons of economic theories, government policies, business strategies, organizational structures, etc. Hill's: International Business goes beyond the often shallow explanations that other books offer, while maintaining a tight integrated flow between the chapters. Hill's book is practical in nature, focusing on the managerial implications of each topic on the actual practice of international business. The author's passion and enthusiasm for the international business arena is apparent on every page as he strives to make important theories interesting, informative, and accessible to all students.
Keywords: Hợp tác, quốc tế,International business enterprises,Competition, international; Management